Role of Anti-oxidants in the Treatment of Vitiligo - Kumar, Amit; Agrawal, Sudha; Dhali, Tapan Kumar; Majhi, Shankar Kumr (Nepal Journal of Dermatology, Venereology & Leprology, 2019)
Introduction: The role of free radicals and oxidative damage in the pathophysiology of vitiligo has been documented in recent studies. Antioxidant supplementation has been reported to be useful in the treatment of vitiligo. Objective: To evaluate the role of oral antioxidants supplementation therapy in the treatment of vitiligo by assessing the onset of repigmentation and oxidative stress. Materials and Methods: A total of 80 cases of vitiligo randomized into two groups: antioxidant and placebo comprising 40 patients each and were followed up for 8 weeks for the assessment of onset of repigmentation of vitiliginous lesions as primary outcome. The activities of Malondialdehyde (MDA), Vitamin C, and Vitamin E in serum and of Catalase (CAT) in erythrocytes of patients at baseline and at end of eight weeks were also assessed by using the spectrophotometric assay. Results: The onset of repigmentation was noted significantly earlier among the anti-oxidant group as compared to the placebo group (p=0.015). At the baseline, between the two groups, no significant difference was found in the different biochemical parameters. However, at the end of 2 months the level of MDA (p<0.001) was found to be significantly lower and that of Vitamin E (p<0.001) and CAT (p=0.005) was significantly higher among the anti-oxidants group as compared to the placebo group. Conclusion: Antioxidant supplementation carried a better response in terms of early onset of repigmentation and significant decrease in the oxidative stress, in the short follow up of two months.